On factors controlling precursor slip fronts in the laboratory and their relation to slow slip events in nature. Issue 6 (31st March 2017) - Selvadurai, Paul A.; Glaser, Steven D.; Parker, Jessica M.
Abstract: Spatial variations in frictional properties on natural faults are believed to be a factor influencing the presence of slow slip events (SSEs). This effect was tested on a laboratory frictional interface between two polymethyl methacrylate (PMMA) bodies. We studied the evolution of slip and slip rates that varied systematically based on the application of both high and low normal stress ( σ 0 =0.8 or 0.4 MPa) and the far‐field loading rate ( V LP ). A spontaneous, frictional rupture expanded from the central, weaker, and more compliant section of the fault that had fewer asperities. Slow rupture propagated at speeds V slow ∼0.8 to 26 mm s −1 with slip rates from 0.01 to 0.2 μm s −1, resulting in stress drops around 100 kPa. During certain nucleation sequences, the fault experienced a partial stress drop, referred to as precursor detachment fronts in tribology. Only at the higher level of normal stress did these fronts exist, and the slip and slip rates mimicked the moment and moment release rates during the 2013–2014 Boso SSE in Japan. The laboratory detachment fronts showed rupture propagation speeds V slow / V R ∈ (5 to 172) × 10 −7 and stress drops ∼ 100 kPa, which both scaled to the aforementioned SSE. Distributions of asperities, measured using a pressure sensitive film, increased in complexity with additional normal stress—an increase in normal stress caused added complexity by increasing both the mean size and standard deviation of asperity distributions, and this appeared to control the presence of the detachment front. Key Points: Quasi‐static precursors are observed in the laboratory and the rupture speed and stress drop scaled to slow slip events (SSEs) in nature Precursors only appeared at higher fault normal stress and showed similar slip evolution patterns to the 2013–2014 Boso SSE in Japan A novel friction law promotes the destabilization of a quasi‐static precursor with increased normal stress, which followed our experiments